How does education policy reform affect schooling outcomes? Novel evidence from Nigeria - Elom, Chinyere Ori; Amadi, Mark Umunna; Uwaleke, Chidebe Chijioke; Onyeneke, Robert Ugochukwu (Edelweiss Applied Science and Technology, 2025)
This study evaluated the effects of the Universal Basic Education (UBE) policy on schooling outcomes in Nigeria. We analyzed the effects of the UBE policy of 2004 on school enrollment outcomes for primary and junior secondary school-age children in Nigeria using two waves (2004 and 2015) of the Nigeria Education Data Survey (NEDS). We applied descriptive statistics to estimate the Net Enrollment Rate (NER) and Age-Specific Enrollment Rate (ASER) and ordered logit regression to model the effect of this policy. The findings revealed that the enrollment rates increased generally in primary schools in southern Nigeria and increased in junior secondary schools (JSS) all over the country in the two periods. The change in NER was positive and significant for JSS enrollment, but insignificant in primary school enrollment. The significant increase in the enrollment of children in primary and junior secondary schools shows the contribution of appropriate policies in improving schooling outcomes. This paper contributes to the body of knowledge on the effects of education policies and programs on schooling outcomes. The paper offered policy recommendations to further improve school enrollment and reduce the high rate of out-of-school children in the country.